Improving Students' Reading Skills Using Image Media At Class I Of SDN 007 Simandolak Riau Province - Fanni Hariyanti Usfa; Muhammad Ali Akbar (International Journal of Technology and Education Research, 2023)
This study aims to (1) improve students' initial reading skills, (2) find appropriate learning steps based on the application of media images as learning media, and (3) find out students' responses to the application of media images as learning media. This research was made in the form of classroom action research using two cycles. The subjects of this study were 17 class I students at SDN 007 Simandolak, Benai District, Kuantan Singingi Regency. Data collection was carried out using observation methods and action tests using reading ability test instruments with predetermined indicators. The data obtained were analyzed by descriptive qualitative. The results showed: the average reading ability of students in the first cycle was 65.85 and the level of mastery percentage reached 55% with a moderate level of ability. In cycle II, the average reading ability of students increased to 76 and the level of proficiency was already relatively high with a completeness level of 85% according to the target set by the researcher, namely 80%. Based on the results of data analysis, it can be concluded that the application of media images in learning can improve students' reading skills in class I SDN 007 Simandolak.